Analysis of transducers arrays from piezoelectric hollow spheres - Hladky-Hennion, A. C.; Alkoy, Sedat; Markley, Douglas C.; Newnham, Robert E.; Meyer, Richard J.; Hughes, W. Jack; Cochran, Joseph K. (My University, 2002)
This paper describes the design and the development of transducer arrays fabricated from miniature piezoceramic hollow spheres, the BBs. After the presentation of the fabrication procedure of the transducers, it presents the numerical tools used to model 2×2 and 4×4 transducer arrays in water. Numerical calculations give good agreement with the experimental results and provide physical insight for understanding the acoustic observations. © 2004 Elsevier Science B.V., Amsterdam. All rights reserved.
2002 IEEE Ultrasonics Symposium -- Munich -- 60922
Keywords: Acoustic arrays; Electrodes; Hydrophones; Spheres; Piezoelectric hollow spheres; Transducer arrays; Piezoelectric transducers